Key Factors Shaping Students’ E-Learning Satisfaction in Higher Education: A Study in Chengdu, China - cheng, Yanzhi (Scholar: Human Sciences, 2026)
Purpose: This research aimed to enhance student satisfaction by fostering social presence, quality of service, information, learner, and perceived usefulness. Research Design, Data, and Methodology: The sample was 80 full-time students from the three main colleges of Xihua University. The change level was determined by conducting the same questionnaire before and after the strategic plan (SP). The data was analyzed, and the hypotheses were tested using mixed methods research. Experts conducted the item-objective congruence (IOC) test and pilot test, and multiple linear regression (MLR) indicated that mean values change significantly for those six variables between pre- and post-SP. The strategic plans included team establishment, goal setting, SWOT analysis, policy support, and course program. Results: Findings from qualitative research methods proved improvements in all variables between the pre-and post-SP. Additionally, innovative approaches to improving student satisfaction are discussed, along with recommendations and limitations for future research. Conclusions: Learners’ attitudes and self-discipline play crucial roles in influencing satisfaction with online learning. A negative learning attitude, reluctance to engage in online platforms, a tendency to passively absorb information in traditional settings, and a lack of initiative are key factors that diminish satisfaction in online learning environments.